Leucine zipper downregulated in cancer 1 may serve as a favorable prognostic biomarker by influencing proliferation, colony formation, cell cycle, apoptosis, and migration ability in hepatocellular carcinoma - Chen, Huaping; Chen, Siyuan; Chen, Chen; Li, Aifeng; Wei, Zhixiao (Frontiers in Genetics, 2022)
Aims: Leucine zipper downregulated in cancer 1 (LDOC1) inhibits tumor growth in several cancers. However, the expression and function of LDOC1 in hepatocellular carcinoma (HCC) remain unknown. In this study, we aimed to investigate how LDOC1 influenced tumor progression and the biological functions of HCC. Methods: The transcription levels of LDOC1 were determined using the GEPIA and UALCAN online databases and a real‐time polymerase chain reaction. Western blot and immunohistochemistry were used to validate the protein levels of LDOC1. The online Kaplan-Meier Plotter was applied for survival analysis. Lentivirus transfection was used to construct LDOC1 exogenous overexpression cell lines. Proliferation, clone formation, cell cycle, apoptosis, and migration assays were performed with the LDOC1-upregulated Huh7 and Hep3B cell lines. The phosphorylated and total levels of AKT and mTOR were determined using a Western blot to explore the potential molecular mechanism of LDOC1. Results: In the GEPIA and UALCAN analyses, LDOC1 was lowly expressed in tumors and had high expression in normal tissue samples (P < 0.05), and negatively correlated with tumor grade progression. The down-regulation of LDOC1 in HCC was validated with real‐time polymerase chain reaction, Western blot, and immunohistochemistry (all P < 0.05). LDOC1 transcription levels were negatively associated with overall, progression‐free, recurrence‐free, and disease‐specific survival (all P < 0.05). The functional experiments suggested that the overexpression of LDOC1 contributed to increased G1 and G2 stages in Huh7, while increased G2 stage in Hep3B, and decreased cell proliferation, clone formation, and migration, as well as increased the apoptosis rate compared with a control group (all P < 0.05). Furthermore, LDOC1 up-regulation reduced the p-AKT/AKT and p-mTOR/mTOR, which indicates an inactivation of the AKT/mTOR pathway. Conclusion: The tumor-suppressor LDOC1 varied in HCC and non‐HCC tissues, which can serve as a candidate prognostic biomarker. LDOC1 influenced survival by affecting proliferation, colony formation, cell cycle, apoptosis, and migration ability, which might be attributed to the AKT/mTOR inhibition in HCC.